ANALYSIS OF THE IMPLEMENTATION OF MOTOR VEHICLE TAX RELIEF IN OPTIMIZING REGIONAL REVENUE AT THE REGIONAL REVENUE AGENCY OF NORTH SULAWESI PROVINCE - Dian Ceacilia Fabiola Rattu; Heince R. N. Wokas; I Gede Suwetja (Universitas Sam Ratulangi, 2022)
The granting of tax relief is a program of reducing, eliminating or amending tax penalties imposed on vehicle owners. This study aims to analyze the application of motor vehicle tax relief to optimize regional income to meet these objectives, planning and efforts must be made as well as tips for optimizing revenue. The type of research used is a qualitative with descriptive approach. The data obtained are by conducting interviews, observation and documentation. The data analysis method used is a descriptive analysis by collecting and classifying data, then analyzing it, so that it can produce a conclusion to answer the existing problems. The results showed that the granting of motor vehicle tax relief can optimize regional income and also increase taxpayer awareness of paying taxes.